Attitude, Acceptability and Knowledge of HPV Vaccination among Local University Students in Hong Kong - Chiang, Vico Chung Lim (Int J Environ Res Public Health, 2016)
The Human Papillomavirus (HPV) vaccine has the great potential to prevent HPV-related infections for millions of women and men worldwide. However, the success of the vaccine is highly dependent on the vaccination rate. Factors influencing the attitudes of undergraduate students towards HPV vaccination should be studied. This is a cross-sectional survey that was conducted to estimate the HPV vaccination rate among undergraduate students in Hong Kong, and to identify the predictors of their attitude towards HPV vaccination. The results showed that the HPV vaccination rate was 13.3%. Factors related to knowledge of vaccination were the main predictors of the students’ attitude towards vaccination (there were seven predictors, with B = 1.36 to 2.30; p < 0.05), followed by gender (B = −1.40; p < 0.05), acceptable maximum price (B = 0.35; p < 0.05), and willingness to receive the HPV vaccine if it can protect against cervical/anal cancer and genital warts (B = −1.90; p < 0.001). The regression model that was developed based on the predictors had a moderate effect size (adj-R(2) = 0.33). To conclude, the HPV vaccination rate among undergraduate students in Hong Kong was low. They should be provided with more active education and activities to promote HPV vaccination to improve their knowledge on the subject.